2011
DOI: 10.1186/1743-422x-8-171
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E Virus infection in HIV-infected patients with elevated serum transaminases levels

Abstract: Increases in aminotransferases levels are frequently encountered in HIV-positive patients and often remain unexplained. The role in this setting and natural history of hepatitis E in HIV-infected patients are unknown. The aim of the study was to assess HEV infection in HIV-infected patients attending a Parisian hospital, with a current or previous cryptogenic hepatitis.191 plasma samples collected from 108 HIV-infected patients with elevated aminotransferases levels were retrospectively tested for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 15 publications
0
32
1
Order By: Relevance
“…More recent studies focusing on detection of anti-HEV IgM, IgG, or RNA have identified both acute (266,(303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313) and chronic (266,(268)(269)(270)(271)(272)(273)(274) HEV infections in HIV-positive patients, though it remains unclear whether or not seroprevalence is any greater in people with HIV (272,273,300,309,310,(314)(315)(316)(317)(318). Chronic HEV infections in HIV-positive individuals have been associated with quick progression to cirrhosis (269)(270)(271), though it is not clear whether HEV-linked cryptogenic cirrhosis is more common in HIV-infected individuals than in the general population (310,311,315,319).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…More recent studies focusing on detection of anti-HEV IgM, IgG, or RNA have identified both acute (266,(303)(304)(305)(306)(307)(308)(309)(310)(311)(312)(313) and chronic (266,(268)(269)(270)(271)(272)(273)(274) HEV infections in HIV-positive patients, though it remains unclear whether or not seroprevalence is any greater in people with HIV (272,273,300,309,310,(314)(315)(316)(317)(318). Chronic HEV infections in HIV-positive individuals have been associated with quick progression to cirrhosis (269)(270)(271), though it is not clear whether HEV-linked cryptogenic cirrhosis is more common in HIV-infected individuals than in the general population (310,311,315,319).…”
Section: Immunosuppression and Impaired Viral Clearancementioning
confidence: 99%
“…In contrary, in severely immunosuppressed patients chronic HEV infection could be a cause of persistent alanin aminotransferase (ALT) elevation. So, HEV persistence may be a potential risk of disease progression also in HIVinfected patients [13][14][15][16][17]. HEV infection needs to be considered as a possible cause of unexplained increase in liver enzymes when common viral causes of hepatitis are excluded.…”
Section: Introductionmentioning
confidence: 99%
“…HEV transmission through sexual intercourse between MSM had been suspected in the 1990s but was not confirmed thereafter (19,21,28). Nonetheless, HEV transmission may potentially occur through sexual intercourse between MSM, as demonstrated for HAV or HCV, particularly in HIV-seropositive persons (29)(30)(31), and HEV infection has been described previously in several MSM and a bisexual man infected with HIV (9,17,21,32,33). Here, the patient reported sexual intercourse with several men and concurrently acquired HBV as well as HAV and HIV earlier in his life.…”
mentioning
confidence: 99%